Studies of the Surface Properties of an MCM-41 Molecular Sieve Using Thermal Analysis and Nitrogen Adsorption Methods - P. Staszczuk; T. Danielkiewicz; J. Klinowski (Adsorption Science & Technology)
The Q-TG mass loss and first derivative Q-DTG mass loss curves with respect to temperature and time obtained during programmed liquid thermodesorption under quasi-isothermal conditions have been used to study adsorbed layers on and the heterogeneous properties of an MCM-41 molecular sieve. The values of the adsorption capacity, total porosity of the material, discontinuous charges in adsorption layer properties and changes in the mechanism of the wetting process have been determined. The porosity parameters of the samples studied were also determined from nitrogen adsorption measurements. The total pore volumes of the tested samples were compared with thermogravimetric data with good correlations being obtained.